External Doping Effects in Competitive Weightlifting - Laprade, Graeme (Université d'Ottawa | University of Ottawa, 2018)
This study uses results from the International Weightlifting Federation world championships to examine the peer effects of doping in competitive weightlifting. The sport of weightlifting provides a controlled environment and an objective measure of performance, as well as an abundance of positive drug test results to analyse how athletes respond to the expulsion of their peers from competition. Athletes can foresee a change in competition due to doping and modify training behaviour or drug use accordingly. Ifind that the doping level of an athlete's direct competitors is negatively related to performance.